The Impact of the Russian Invasion of Ukraine on the Economic Sector in Indonesia - Susanto, Fathima Aulia Vasya; Paksi, Arie Kusuma (Insignia: Journal of International Relations, 2023)
This research discusses the impact of Russia's invasion of Ukraine on the Indonesian economy, focusing on the energy sector. Amidst the increasing complexity of global geopolitical issues, international events such as Russia's invasion of Ukraine have significant global consequences, even for countries not directly involved in the conflict. This study is grounded in the theory of the political economy of war, serving as the analytical framework to understand how these dynamics affect Indonesia's economic sector. As a direct consequence of the invasion, the global energy sector distribution has been disrupted. Nations that previously imported energy from Russia must now seek alternative sources to meet their energy needs. Indonesia, being one of the world's largest producers of non-oil and gas energy, emerges as a primary choice of alternative energy export source. The research findings indicate a substantial increase in the export of non-oil and gas energy from Indonesia, which, in turn, has a positive impact on the growth of the country's economic sector. The research employs a descriptive-qualitative approach, collecting data from literature reviews and online research to complement secondary data. The results of this study offer insights into how changes in global geopolitical dynamics can affect a country's economy, even when not directly involved in such events. Indonesia, for instance, has seized the opportunity to boost its non-oil and gas energy exports, thereby influencing the growth of a specific economic sector in the country. This research provides valuable contributions to understanding the interplay between geopolitical events and the global economy. Keywords: economic, Indonesia, invasion, Russia, Ukraine